Difficult to treat microorganisms in patients aged over 80 years with community-acquired pneumonia: the prevalence of PES pathogens. Issue 4 (8th October 2020) - Cilloniz, Catia; Dominedo, Cristina; Peroni, Héctor José; Di Giannatale, Pierluigi; Garcia-Vidal, Carolina; Gabarrus, Albert; Liapikou, Adamanthia; Ceccato, Adrian; Torres, Antoni
In 2015, in a cohort of immunocompetent adults, we reported PES pathogens ( Pseudomonas aeruginosa, extended-spectrum b-lactamase-producing Enterobacteriaceae, and methicillin-resistant Staphylococcus aureus ) in 6% of patients with community-acquired pneumonia (CAP) and microbiological diagnosis. We proposed the use of the PES score, as described previously [1], to assess the risk of pneumonia due to PES pathogens. The score was shown to have good accuracy, with an area under the receiver operating characteristic curve (AUC) of 0.754 (0.708–0.801). We therefore decided to investigate the frequency and characteristics of CAP caused by PES pathogens in late elderly (≥80 years old) patients with CAP. This study demonstrates the importance of identifying patients over 80 years old at risk of CAP due to PES pathogens in order to initiate adequate antimicrobial therapy https://bit.ly/2zuWPvx